حكم التصويت للأصلح في الانتخابات: The Ruling on Voting for the Most Qualified Candidate in the Elections - AbdolQassim, Nasir; Syed Ismail, Sharifah Hayaati; Mahyoub Murshed, Amer Abdulwahab (Jurnal Fiqh, 2022)
This study addresses the issue of ruling on voting for the most qualified candidate in elections which is one of the important issues in the present time and requires deliberation from Muslim scholars. This issue has led to different opinions and divisions among people in a single country. Hence, the major question in this study; what is the position of Islamic jurisprudence in terms of voting for a highly qualified candidate? It is an important question as it relates to governance and seigniory which also concerns all people who take part in elections as the consequences may affect the community. Hence, this study aims to clarify the issue of voting for a highly qualified candidate in elections by gathering and analyzing contemporary researchers’ views and arguments to reach a superior jurisprudent summary. This study also aims to obtain the most appropriate opinion that fits the purposes of Islamic law and the current situation. To achieve the objective, this study employed analytical, deductive, and inductive methodologies. This study concludes that voting for the fittest character is considerable for necessity since it relies on significant sharia evidence and rules such as: Necessities permit prohibitions. And the researcher recommends those people who are working in the field of religious calling to participate actively in elections and not boycotting due to the Muslims afflictions in the last few decades. If they know that there is a qualified person who can serve Islam and Muslims and decrease evil or corruption, they should vote for him, otherwise it is better to step down.